Les études et recherches lesbiennes et gays en France (1970-2006) - Régis Revenin (Genre & Histoire)
This article presents a non-exhaustive overview of gay and lesbian studies and research in the social sciences and humanities (principally in history) that have been undertaken in France, both within and outside of the French university system, from the beginning of the 1970s until recently. Within the broader context of work on sexuality, there has been a significant increase in LGBTQ (Lesbian, gay, bi, trans and queer) studies, in a wide variety of academic disciplines and subjects, since the early 2000s. However, while increasingly visible within the media, this field of research still remains very marginal within the French university system, and nowhere in France is there a specific department or program in humanities or in the social sciences dedicated to LGBTQ studies or even to the study of human sexuality.